DAMPAK PANDEMI COVID 19 TERHADAP PERKEMBANGAN USAHA MIKRO DI KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Indah Tri Laduni; Nuraini Asriati; Ludovicus Manditya Hari C (Universitas Tanjungpura, 2022)
This study aims so that we can find out the Impact of the Covid-19 Pandemic on the Development of UMKM in Rasau Jaya District, Kubu Raya Regency. The research method used is quantitative research in the form of descriptive research and case studies. The source of the research data used is the data of UMKM in the District of Rasau Jaya. The results of this study indicate that at the time of the covid-19 pandemic, UMKM actors really felt the impact of the pandemic because of a decrease in income compared to before the pandemic. In addition, there is public reluctance in buying processed products by UMKM actors. So that UMKM actors must have a strategy to overcome the greater impact of the pandemic so that most UMKM actors renew products such as food that have never been sold before and carry out discounts or price cuts. For the assistance provided by the government during the COVID-19 pandemic, not all UMKM actors in Rasau Jaya Sub-district received this assistance, even though the assistance was very helpful for UMKM actors who experienced a decline in income.